Performance of Educational Personnel Which Affected by the Work Environment, Individual Characteristics and Ability as Intervening - Safrida,; Fahmi, Nur Augus; Nasution, Ismail (Archives of Business Research, 2021)
This research talks about Work Environment and Individual Characteristics towards their performance and ability as intervening variables at Educational Staff of Economic Faculty UISU Medan. Based on the results of data analysis by using Path Analysis, it is found out that; Work Environment has positive and significant effect towards the ability; Individuals’ characteristics have positive and significant effect towards Performance; Individuals’ characteristics have positive and significant effect towards performance; Individuals’ characteristics have positive and significant effect towards Performance; and ability has positive and significant effect towards performance. From the results of this research, it is expected that the future researchers conduct research in order to know the factor which has effect towards performance beside work environment, Individuals’ characteristic, and ability.